Efficacy and safety of apremilast versus dapsone versus colchicine in recurrent aphthous stomatitis: a three arm double blinded comparative study - Yadav, Dinesh Kumar; Arora, Aakanksha; Yadav, Ashish (International Journal of Research in Medical Sciences, 2024)
Background: Recurrent aphthous stomatitis (RAS) is often considered as an incurable ailment. Therefore, an effective management option is required for controlling the symptoms and severity of RAS. We aimed to conduct a study to compare the effectiveness and safety profile of apremilast, dapsone and colchicine in management of RAS. Methods: This three-arm double blinded comparative study included 60 cases of recurrent aphthous stomatitis (RAS). Twenty patients each were randomly allocated in three groups: group A (apremilast), group B (dapsone) and group C (colchicine). Results: At the end of 6 weeks, the complete response was seen in 6 (30%) patients in group A as compared to 2 (10%) and 4 (20%) patients in group B and C (p >0.05). At the end of 12 weeks, response rate became statistically significant (p=0.003) with complete response in 14 (70%) of patients. Median time to recurrence, defined as oral ulcer after loss of complete response, was significantly increased to 4.3 weeks in group A as compared to group B and C. The most commonly encountered side effects were gastrointestinal in all three groups. None of the adverse effects resulted in discontinuation of treatment, hospitalization or death in any patient. Conclusions: Although, traditional therapies like dapsone and colchicine have been commonly used in clinical practice, apremilast yielded a rapid and maintained improvement of RAS.